2015
DOI: 10.1109/tmc.2014.2385097
|View full text |Cite
|
Sign up to set email alerts
|

FlierMeet: A Mobile Crowdsensing System for Cross-Space Public Information Reposting, Tagging, and Sharing

Abstract: Community bulletin boards serve an important function for public information sharing in modern society. Posted fliers advertise services, events, and other announcements. However, fliers posted offline suffer from problems such as limited spatial-temporal coverage and inefficient search support. In recent years, with the development of sensor-enhanced mobile devices, mobile crowd sensing (MCS) has been used in a variety of application areas. This paper presents FlierMeet, a crowdpowered sensing system for cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(57 citation statements)
references
References 45 publications
0
56
0
1
Order By: Relevance
“…In this work, the evaluation of our algorithms is based on a real-world human mobility dataset. We are now collaborating with the local government to build a city-level MCS platform for citizens to report municipal problems (e.g., road collapse, public facility damage, and noise disturbance), urban dynamics (e.g., traffic jams, accidents, public information [39]), etc. We intend to introduce our multi-task allocation framework in the platform and make large-scale user studies, which will help identify practical issues and improve our framework.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the evaluation of our algorithms is based on a real-world human mobility dataset. We are now collaborating with the local government to build a city-level MCS platform for citizens to report municipal problems (e.g., road collapse, public facility damage, and noise disturbance), urban dynamics (e.g., traffic jams, accidents, public information [39]), etc. We intend to introduce our multi-task allocation framework in the platform and make large-scale user studies, which will help identify practical issues and improve our framework.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the sequence of S C includes service description complexity SD C , service object space location complexity SS C , service object dynamic form complexity SF C , and computational complexity C C . Among them, it is the key factor to restrict the performance of the system, which can be described by the formula (9).…”
Section: Mobile Geographic Crowd Service Modelmentioning
confidence: 99%
“…An incentive mechanism was proposed by Yutian Wen et al [8] based on a quality-driven auction, which is specifically for the mobile crowd sensing system. In an article [9], a crowd-powered sensing system was presented for crossspace public information reposting, tagging, and sharing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research and applications, e.g. CreekWatch [2], GarbageWatch [3], SmartEye [4], PhotoCity [5], WreckWatch [6], FlierMeet [7], Mediascope [8], iMoon [9] and SakuraSensor [10], indicated that MCP is useful and superior to traditional approaches in visual sensing, e.g. deployment of static cameras for monitoring.…”
mentioning
confidence: 99%
“…buildings [5], flyers [7] and event [28]) and coverage requirements (e.g. the target sensing area and time period, single-shot or multi-shots including different shooting directions [18]).…”
mentioning
confidence: 99%